2020 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2020
DOI: 10.1109/cvpr42600.2020.00444
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Path Region Mining for Weakly Supervised 3D Semantic Segmentation on Point Clouds

Abstract: Semantic segmentation on 3D point clouds is an important task for 3D scene understanding. While dense labeling on 3D data is expensive and time-consuming, only a few works address weakly supervised semantic point cloud segmentation methods to relieve the labeling cost by learning from simpler and cheaper labels. Meanwhile, there are still huge performance gaps between existing weakly supervised methods and state-of-the-art fully supervised methods. In this paper, we train a semantic point cloud segmentation ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 51 publications
1
128
0
Order By: Relevance
“…Finally, the trained model is used to infer the semantic labels of the raw point clouds. Note that, we are aware that the generated pseudo labels are not completely correct, but similar to [48], we found that the final segmentation results are totally acceptable, even trained with these flawed labels.…”
Section: Refining Pseudo Labels For Model Trainingsupporting
confidence: 59%
See 3 more Smart Citations
“…Finally, the trained model is used to infer the semantic labels of the raw point clouds. Note that, we are aware that the generated pseudo labels are not completely correct, but similar to [48], we found that the final segmentation results are totally acceptable, even trained with these flawed labels.…”
Section: Refining Pseudo Labels For Model Trainingsupporting
confidence: 59%
“…That is, learning semantics from other indirect formats of weak supervision or a small fraction of labeled points. MPRM [48] and SegGroup [40] are proposed to generate pseudo pointlevel labels from subcloud-level labels or seg-level labels. SQN [19], Xu's work [55] and SceneContrast [18] are introduced to learn semantic segmentation from a small fraction of randomly annotated or actively labeled points.…”
Section: Chairmentioning
confidence: 99%
See 2 more Smart Citations
“…The multi-path region mining (MPRM) [6] model leverages class activate map to explore object localization cues from weak labels that indicates categrories of input spherical point samples at inexact sub-cloud level, different attention mechanisms are explored to learn a point cloud scene segmentation network by mining long-range spatial context, channel inter-dependency and global context on raw 3D data. But the limited number of pooling layers will inevitably restrict the size of receptive field thus hard for complex scene abstraction.…”
Section: Introductionmentioning
confidence: 99%